Leishmaniasis in Sri Lanka: The need for effective targeting of island-specific issues through strategic implementation of global management plans for disease detection and control - J. M. N. J. Jayathilake; A. W. Taylor-Robinson (Sri Lankan Journal of Infectious Diseases, 2020)
Leishmaniasis, a vector-borne parasitic disease caused by Leishmania sp., has become a considerable global public health burden in recent decades, such that it is recognized by the World Health Organization as one of eight major neglected tropical parasitic diseases worldwide. The causative protozoan parasite is detected on every continent except Antarctica. There are three clinically distinct forms of leishmaniasis: cutaneous, mucocutaneous and visceral, the latter being the most serious manifestation.   In Sri Lanka, at the turn of this century, leishmaniasis was limited initially to a few imported cases but it is now a growing healthcare concern that is endemic to almost all districts. In particular, Hambantota, Matara, Kurunegala and Anuradhapura are seriously affected. Socioeconomic conditions, population mobility, environmental and climate changes are each considered important influences on the prevalence of leishmaniasis throughout the island nation. However, significant knowledge gaps remain regarding the precise epidemiology and severity of the disease, in large part due to the asymptomatic nature of the infection. Development of effective diagnostic tools, mapping disease distribution in unexplored locations and implementation of strategic management plans are all needed to meet the formidable challenge of eliminating leishmaniasis from Sri Lanka.